Synthesis, Crystal Structure and Luminescene of Zinc(II) Complex with 2,6-Pyridinedicarboxylic Acid Radical and 1,10-Phenanthroline - Chen, Shu-Yang; Huang, Yun-Rui; Guo, Ying-Chen; Feng, Yu-Quan (Asian Journal of Chemistry, 2014)
A new zinc(II) complex, [Zn(pydc)2]·[Zn(phen)2(H2O)2]·7.5H2O, has been synthesized by the reaction of zinc sulfate, 2,6-pyridinedicarboxylic acid (pydcH2) and 1,10-phenanthroline (phen) and characterized by elemental analysis, IR, UV-visible, TG and X-ray single-crystal diffraction. It crystallizes in triclinic, space group P`1 , with a = 1.0091 (3), b = 1.4799 (4), c = 1.4984 (4) nm, a = 73.783 (4), b = 78.374 (4), g = 74.886 (4)°, V = 2.0543 (9) nm3, C28H41N6O17.5Zn2, Mr = 992.36, Z = 2, Dc = 1.574 Mg/m3, g(MoKa) = 0.071073 nm, μ = 1.252 mm-1, F (000) = 984, S = 1.040, the final R = 0.0412 and wR = 0.1335 for 6128 observed reflections (I > 2s (I)). The structure unit of the complex consists of two zinc ions with different coordination modes. Each 6-coordinated geometry of the Zn atom is a distorted octahedral coordination geometry. The complex shows a strong fluorescence emission at around 367 nm in methanol solution (CCDC: 848466).